Government Collaboration in Combating Schistosomiasis in Bada - M. Nur Alamsyah; Muhammad Nawawi; Sisrilnardi Sisrilnardi (LAFADZ JAYA Publisher, 2023)
Schistosomiasis is an endemic disease in Indonesia which is only found in the province of Central Sulawesi, namely in Poso and Sigi Regencies. The area where the distribution of sichistosomes was found was in Kab. Poso in three places namely Bada, Lore and Napu. Although the policy for handling schistosomiasis snails and the impact of the disease has been handled since the colonial era, the Indonesian government has only taken serious action since 1982, which has not been completed until now. The absence of a common view on the problem of schistosomiasis has resulted in an asynchronous implementation of programs and activities related to the alleviation of schistosomiasis. This primary data collection technique also uses secondary data that comes from the Poso health office, the Bada schistosomiasis laboratory and the implementation of triangulation of actors, methods and data through focus group discussions which are expected to be able to map out the issues of involvement and the similarity of viewing problems in the management of schistosomiasis control in the context of the study This takes the area of Bada which is relatively successful although not yet complete. The collaboration model by collaborating with various internal institutional elements of the local government in each related regional apparatus organization, involving the community as an important part by becoming stool collectors, the presence of teachers and priests who provide strengthening information regarding the urgency of participation and collaboration to solve schistosomiasis has a broad impact on program achievements this.